Field Evaluation Of Some Insecticides Against White Grub, Lepidiota Mansueta B. (Coleoptera: Scarabaeidae), On Potato (Solanum Tuberosum) In Assam (India) (Applied Biological Research, 2017)
Field studies were conducted to evaluate the efficacy of six insecticides  against white grub, Lepidiota mansueta, in potato in 2012 and 2013 at  Majuli river island in Assam (India). All the insecticide treatments  significantly reduced tuber damage as against untreated control. Of the  insecticides tested, fipronil 5 SC @ 150 g a.i. ha-1 showed low tuber  damage on weight basis (5.24 and 4.57%) and was at par with fipronil 5  SC @ 100 g a.i. ha-1 (5.91 and 5.09%), chlorpyriphos 20 EC @ 400 g a.i.  ha-1 (5.55 and 6.2%) and quinalphos 25 EC @ 400 g a.i. ha-1 (6.14 and  6.72%). On number basis, fipronil 5 SC @ 150 g a.i. ha-1 showed lowest  tuber damage (4.2%), followed by chlorpyriphos 20 EC @ 400 g a.i. ha-1  (5.25%) and quinalphos 25 EC @ 400 g a.i. ha-1 (5.66%). All insecticide  treatments were at par in tuber yield, except emamectin benzoate 5% SG  @ 12.5 g a.i. ha-1. Highest cost benefit ratio was observed in chlor pyriphos 20 EC @ 400 g a.i. ha-1 treatment (2.50 and 2.62), followed by  quinalphos 25 EC @ 400 g a.i. ha-1 (2.23 and 1.85). Chlorpyriphos 20 EC  @ 400 g a.i. ha-1 and quinalphos 25 EC @ 400 g a.i. ha-1 seem better  alternatives than fipronil to reduce infestation of L. mansueta in potato.
Keywords: Insecticides; potato; white grub; Lepidiota mansueta